Variable frequency control of the resonant half bridge dual converter - Li, Q.; Wolfs, Peter (University of Canterbury NZ, 2003)
The resonant half bridge dual converter has been previously developed for the DC-DC conversion application in a two-stage photovoltaic Module Integrated Converter (MIC). In order to apply Maximum Power Point Tracking (MPPT) for the PV module or provide variable output voltage, the DC-DC converter is required to operate with variable input/output voltage ratios. This paper studies the variable frequency control of the resonant half bridge dual converter, which is able to produce an output voltage range of 1:2.3 while maintaining resonant switching transitions. The design method of the converter is analysed in detail and the explicit control functions for a 200 W converter are established. Both of the theoretical and simulation waveforms are provided. A resonant half bridge dual converter with the voltage clamp is also proposed at the end of this paper.